ENGLISH: ENGLISH - Šljivančanin Jakovljević, Tamara (Medical Research, 2023)
Introduction/Aim: Respiratory distress (RD) is the most common reason for morbidity in preterm infants. The current study was undertaken to determine causes of RD in late preterm infants, analyze characteristics of RD regarding gestational age, compare different clinical forms of RD and determinate the factors that influence the unfavorable outcome of late preterm infants with RD. Methods: Study included infants born between 34 0/7 and 36 6/7 weeks of gestation with RD hospitalizedin the Institute for Mother and Child Health Care of Serbia „DrVukanCupic“. Demographic and clinical characteristics, clinical signs and course of the disease, occurrence of complications, as well as quantification of disease severity were analyzed. The outcome was assessed through the mortality, duration of mechanical ventilation and hospitalizationlenght. Patients are ranked and compared according to gestation and type of RD. Descriptive and analytic statistical methods were used for analysis of study results. Results: A total of 65 latepreterm neonates were included in the study. The majority were male. Respiratory distress syndrome (RDS) (46.2%) and transient tachypnea of the newborn (TTN) (40%) were the most common causes of RD. TTN was the most prevalent in the 36gestational week and RDS before 35 gestational week. An average hospitalization length was 15 days and mortality in the study group was 1.5%. Conclusion: The most common causes of RD in late preterm infants are RDS and TTN. The late preterm infants are vulnerable category of newborns, with a high risk of associated morbidity and mortality.